Identificação molecular de cepas clínicas e ambientais de Burkholderia pseudomallei, oriundas do estado do Ceará : análise baseada nas regiões 16S e 16S-23S do DNA ribossômico nuclear - Couto, Manuela Soares (2009)
Melioidosis is a potentially fatal disease caused by the bacterium Burkholderia pseudomallei, considered emerging in Brazil since the first cases were reported in 2003, on State of Ceará. This study aimed to perform the molecular identification of 31 isolates of B. pseudomallei (26 clinical and 5 environmental) maintained in the culture collection of CEMM (Specialized Center for Medical Mycology), based on sequences 16S and 16S-23S rRNA. The DNA of these samples was extracted with the kit Wizard ® Genomic DNA Purification (Promega), quantified by spectrophotometry and stored at 4°C. The amplification of a fragment of 302 bp of 16S-23S rRNA specific to B. pseudomallei was performed by PCR reaction with primers Bp1 and Bp4. The sequencing of 16S and 16S-23S rRNA was performed by using of the kit DYEnamicTM ET terminators cycle sequencing (GE Healthcare). The phylogenetic tree of 16S rRNA and the sequence identity matrix and sequence difference count matrix based on the 16S-23S rRNA were generated by the program MEGA4, version 4.1. The results confirmed the identification of 15 strains of B. pseudomallei (5 clinical and 10 environmental), which represents 48.4% of the isolates analyzed in this study. The phylogenetic tree based on 16S rRNA shows that the clinical and environmental isolates of B. pseudomallei of State of Ceará are evolutionarily clustered with the strains B. pseudomallei MSHR346 (Australia), B. pseudomallei 1106a (Thailand), B. pseudomallei K96243 (Thailand), B. pseudomallei 1710b (Thailand) and B. pseudomallei 668 (Australia). Using the same extraction kit was possible to extract DNA from B. pseudomallei directly from clinical specimen (bronchoalveolar lavage), confirming a new case of melioidosis in Ubajara/CE. In this study, the use of PCR for amplification of a fragment of 302 bp of 16S-23S rRNA identified correctly B. pseudomallei, and to confirm the discrimination between B. pseudomallei and B. mallei, the sequencing of the 16S and 16S-23S rRNA genes was performed. The technique of PCR coupled with sequencing of 16S and 16S-23S rRNA resulted in a high sensitivity and specificity of detection of B. pseudomallei in this study.